Political risk and macroeconomic effect of housing prices in South Africa - Thomas Habanabakize; Zandri Dickason (Cogent Economics & Finance)
The housing market is one of the key drivers of economic growth and social welfare in South Africa. However, the performance of the market depends on housing prices which are also subjected to changes in various socio-economic and political factors. The main purpose of this study is to determine the effects of inflation (consumer price index), interest rate, rental price and political risk on housing prices. To achieve this objective, the study applies Vector Autoregressive (VAR) model, the Johansen test for cointegration, Vector Error Correction Model (VECM) and Granger causality test on monthly data starting from January 2002 to December 2019. Findings of the study suggest that inflation, interest rate, rental and political risk influence the housing prices in both the long run and short run. Changes in political risk and rental price cause a long-run decline in housing prices while high-interest rates and inflation cause an increase in housing prices. Based on findings, researchers propose stability in the inflation rate, interest rate and political situation as a solution that can assist to improve the housing market and create price stability. Additionally, interest rate reduction can generate growth in housing demand resulting in the country’s economic improvement.